Temporal expression of mitochondrial life cycle markers during acute and chronic overload of rat plantaris muscles - Hyatt, Jon-Philippe K.; Lu, Emilie J.; McCall, Gary E. (Frontiers in Physiology, 2024)
Skeletal muscle hypertrophy is generally associated with a fast-to-slow phenotypic adaptaGon in both human and rodent models. Paradoxically, this phenotypic shi^ is not paralleled by a concomitant increase in mitochondrial content and aerobic markers that would be expected to accompany a slow muscle phenotype. To understand the temporal response of the mitochondrial life cycle (i.e., biogenesis, oxidaGve phosphorylaGon, fission/fusion, and mitophagy/autophagy) to hypertrophic sGmuli, we used the funcGonal overloaded (FO) model in adult female rats and examined the plantaris muscle responses at 1 and 10 weeks. As expected, absolute plantaris muscle mass increased ~12 and 26% at 1 and 10 weeks following the FO procedure. Myosin heavy chain isoforms types I and IIa significantly increased 6.4 and 2.7%, respecGvely, in 10-week FO plantaris muscles. Although there was a general increase in protein markers associated with mitochondrial biogenesis in acute FO muscles, this response was, unexpectedly, sustained in 10week FO condiGons a^er muscle hypertrophy is known to have plateaued. Furthermore, the early rise in mito/autophagy markers observed in acute FO condiGons were normalized by 10 weeks, suggesGng a cellular environment favoring mitochondrial biogenesis to accommodate the aerobic demands of the plantaris muscle. We also observed a significant increase in the expression of mitochondrial-, but not nuclear-, encoded OXPHOS proteins and pepGdes (i.e., humanin and MOTS-c) in chronic, but not acute, FO condiGons. Taken together, the temporal response of markers related to the mitochondrial life cycle indicate a pa5en of promoGng biogenesis and mitochondrial protein expression to support the energy demands and/or enhanced neural recruitment of chronically overloaded skeletal muscle.